Light-curing 3D printed bioceramic bone cartilage scaffold and preparation method thereof

The preparation of double-layer bioceramic bone-cartilage scaffolding through photocuring 3D printing technology has solved the problem of poor stability in the body of the existing scaffolding, achieving long-term stability and effective repair of cartilage damage.

CN119055412BActive Publication Date: 2025-05-02NEO MODULUS (SUZHOU) MEDICAL SCI TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411535652.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-05-02
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing cartilage repair stents are prone to loosening, stratification or disintegration in the body, resulting in failure of repair, and traditional fixation methods are difficult to ensure the long-term stability of the implant.

Method used

The photocuring 3D printing technology is used to prepare a double-layer bioceramic bone-cartilage scaffold, including a cartilage repair layer and a subchondral bone repair layer. The two layers intersect each other at the junction to form a small pore structure, simulate the function of the calcification layer, prevent blood vessel invasion, and improve the mechanical properties and stability of the scaffold by regulating the solid phase volume fraction and viscosity of the printing slurry.

Benefits of technology

The long-term stability of the stent in the body is achieved and the effective repair of cartilage damage is avoided, loosening and stratification are improved, and the repair effect and mechanical properties of the stent are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119055412B_ABST
    Figure CN119055412B_ABST
Patent Text Reader

Abstract

The present application discloses a photocurable 3D printed bioceramic osteochondrium scaffold, which relates to the technical field of tissue repair materials. The scaffold includes a cartilage repair layer and a subchondral bone repair layer formed of the same material. The cartilage repair layer has a porous structure with a first aperture of 100-1000 μm, and the subchondral bone repair layer has a porous structure with a second aperture of 300-1000 μm. The cartilage repair layer and the subchondral bone repair layer are interlaced at the junction to form a pore structure with a third aperture of 50-300 μm; the third aperture is smaller than the first aperture and the second aperture. The osteochondrium scaffold of the present invention can ensure that bone marrow blood carries bioactive substances such as bone marrow mesenchymal stem cells and growth factors to penetrate into the cartilage defect site, and at the same time can hinder the vascular invasion of the subchondral bone repair layer and prevent the calcification of the cartilage layer; the subchondral bone repair layer provides sufficient support for the repair of the cartilage layer during the repair process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical biomaterial preparation and tissue engineering technology, and in particular to a photocurable 3D printed bioceramic bone cartilage scaffold and a preparation method thereof. Background Art

[0002] Articular cartilage is an important structure of human joints and plays an important role in motor function. Due to the special structure of articular cartilage and its poor healing ability, once damaged, it is difficult to self-repair, which seriously affects the motor function of the joint. Many athletes have to say goodbye to their sports careers. For ordinary people, articular cartilage damage usually accelerates joint degeneration, leading to osteoarthritis, which seriously affects the quality of life. Therefore, articular cartilage damage is a common and difficult joint disease in clinical practice. The repair and regeneration of articular cartilage damage has always been a key and difficult topic in the field of sports medicine and orthopedic surgery.

[0003] Traditional cartilage repair surgeries, such as debridement and microfracture, can improve symptoms in some patients, but the new cartilage tissue is usually fibrocartilage, which is not wear-resistant and has poor long-term treatment effects.

[0004] With the advancement of biomaterials science, cell-free scaffold approaches have recently emerged. These scaffolds are made of biomaterials that allow cell adhesion and differentiation to support cartilage tissue regeneration. These scaffolds can be combined with microfracture techniques to cover the bone marrow stimulation site to stabilize the blood clot and enhance the differentiation of cell precursors into chondrocytes. On the other hand, the state of subchondral bone is considered a key factor affecting articular cartilage regeneration. Therefore, a new treatment principle focusing on cartilage and subchondral bone tissue has been developed: an innovative double-layer scaffold was invented and introduced for clinical application. This technology only requires a single surgery and can provide regenerative support for the proliferation and differentiation of resident cells into subchondral bone and cartilage tissue.

[0005] At present, cartilage repair scaffold products can be divided into two types according to their phase structure: gel and multilayer scaffold (membrane). Gel products are usually made of collagen or chitosan gel, such as ChondroFiller, ColtrixCartiRegen, JointRep and BST-Cargel. These products can form gel in situ after being injected into the injured site, with the advantages of minimally invasive and simple surgical operation. However, the mechanical strength of gel is weak and the degradation rate is fast, which is usually not suitable for repairing severe or long-term cartilage damage. Scaffold products are two-layer or three-layer scaffolds or film structures, such as MaioRegen, Chondro-Gide and ChondroMimetic. This type of scaffold usually needs to be fixed by suturing or gluing after implantation. However, due to the large difference in mechanical strength of different layers of the scaffold, weak interlayer bonding strength, and loose fixation, the scaffold may become loose, stratified or even disintegrated in the body, resulting in repair failure.

[0006] The fixation method between the scaffold and the wound is crucial for the successful repair of cartilage. Traditional cartilage scaffold products are fixed by in-situ gelation, gluing or suturing, but due to weak bonding strength and poor mechanical properties, it is difficult to ensure the long-term stability of the implant. Cartiheal's Agili-C uses aragonite scaffolds formed by calcined coral bones as raw materials, and the scaffold has good mechanical properties. However, the raw material of Agili-C is coral bones, and corals are scarce natural resources in my country, and the possibility of large-scale commercial development is very low. In addition, the microstructure of corals after calcination is difficult to control, which is not conducive to product standardization. In order to achieve the expected effect of the product, biomaterials must be injected into it, but this still cannot change the rigid structure of the scaffold itself, which brings many unstable factors to the cartilage repair process. Therefore, it is urgent to find a cartilage scaffold that is firmly fixed to the wound, has good mechanical properties and can ensure the long-term stability of the implant. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a photocurable 3D printed bioceramic bone cartilage scaffold and a preparation method thereof.

[0008] In one aspect, the present invention provides a photocurable 3D printed bioceramic osteochondral scaffold, comprising a cartilage repair layer and a subchondral bone repair layer formed of the same material, wherein:

[0009] The cartilage repair layer comprises a porous structure with a first pore size, wherein the first pore size is 100-1000 μm.

[0010] The subchondral bone repair layer comprises a porous structure having a second pore size, wherein the second pore size is 300-1000 μm.

[0011] The cartilage repair layer and the subchondral bone repair layer are adjacent to each other and are constructed such that: at the junction of the two layers, they are interlaced to form a pore structure with a third pore size, and the third pore size is 50-300 μm;

[0012] Among them, the first aperture, the second aperture and the third aperture meet the following conditions: the third aperture is smaller than the first aperture, and the third aperture is smaller than the second aperture; the size of the third aperture is sufficient to prevent blood vessels from invading the cartilage repair layer.

[0013] In some embodiments of the present invention, the first pore size is 600-800 μm.

[0014] In some embodiments of the present invention, the second pore size is 400-600 μm.

[0015] In some embodiments of the present invention, the third pore size is 100-300 μm.

[0016] In some embodiments of the present invention, the pore wall thickness of the porous structure of the cartilage repair layer is 100-300 μm.

[0017] In some embodiments of the present invention, the pore wall thickness of the porous structure of the subchondral bone repair layer is 200-400 μm.

[0018] In some embodiments of the present invention, the osteochondral scaffold is in the shape of a truncated cone as a whole, wherein the cartilage repair layer forms the upper part of the truncated cone, and the subchondral bone repair layer forms the lower part of the truncated cone.

[0019] In some embodiments of the present invention, the taper of the frustum is 1:100-1:20.

[0020] In some embodiments of the present invention, the cartilage repair layer is mainly composed of a vertical pore structure, which is consistent with the arrangement of chondrocytes.

[0021] In some embodiments of the present invention, the cartilage repair layer is further provided with side holes.

[0022] In some embodiments of the present invention, the porosity of the cartilage repair layer is 50%-80%.

[0023] In some embodiments of the present invention, the porosity of the subchondral bone repair layer is 40%-60%.

[0024] In some embodiments of the present invention, the hole walls of the cartilage repair layer and the subchondral bone repair layer are rounded or chamfered.

[0025] In some embodiments of the present invention, the light-cured 3D printing slurry for forming the cartilage repair layer and the subchondral bone repair layer includes one or more of the following substances: hydroxyapatite, β-tricalcium phosphate, and bioactive glass.

[0026] In some embodiments of the present invention, the solid phase volume fraction of the photocurable 3D printing slurry forming the cartilage repair layer and the subchondral bone repair layer is 40% to 58%.

[0027] In some embodiments of the present invention, the viscosity of the light-cured 3D printing slurry for forming the cartilage repair layer and the subchondral bone repair layer is 400-8580 mP·s.

[0028] On the other hand, the present invention provides a method for preparing a light-cured 3D printed bioceramic bone cartilage scaffold, the preparation method comprising the following steps:

[0029] A scaffold model is established, wherein the scaffold includes a cartilage repair layer and a subchondral bone repair layer, wherein the cartilage repair layer includes a porous structure with a first pore size, and the first pore size is 100-1000 μm; the subchondral bone repair layer includes a porous structure with a second pore size, and the second pore size is 300-1000 μm; the cartilage repair layer and the subchondral bone repair layer are adjacent to each other and are constructed such that: at the junction of the two, they are interlaced to form a pore structure with a third pore size, and the third pore size is 50-300 μm; wherein the first pore size, the second pore size and the third pore size meet the following conditions: the third pore size is smaller than the first pore size, the third pore size is smaller than the second pore size, and the third pore size is sufficient to prevent blood vessels from invading the cartilage repair layer;

[0030] Preparing a printing slurry for a cartilage repair layer and a subchondral bone repair layer, wherein the slurry comprises ceramic powder, a photosensitive resin, a photoinitiator, a light absorber and a dispersant;

[0031] Using printing slurry to form a scaffold embryo through 3D printing;

[0032] The scaffold green body is sintered after post-processing.

[0033] In some embodiments of the present invention, the ceramic powder includes one or more of the following substances: hydroxyapatite, β-tricalcium phosphate, and bioactive glass.

[0034] In some embodiments of the present invention, the solid volume fraction in the printing slurry is 40% to 58%.

[0035] In some embodiments of the present invention, the viscosity of the printing slurry is 400-8580 mP·s.

[0036] In some embodiments of the present invention, the first pore size is 600-800 μm.

[0037] In some embodiments of the present invention, the second pore size is 400-600 μm.

[0038] In some embodiments of the present invention, the third pore size is 100-300 μm.

[0039] In some embodiments of the present invention, the osteochondral scaffold is in the shape of a truncated cone as a whole, wherein the cartilage repair layer forms the upper part of the truncated cone, and the subchondral bone repair layer forms the lower part of the truncated cone.

[0040] In some embodiments of the present invention, the taper of the frustum is 1:100-1:20.

[0041] Compared with the prior art, the present invention has the following beneficial technical effects:

[0042] The present invention designs the porous structure of the cartilage repair layer and the subchondral bone repair layer formed of the same material, and makes the two interlace with each other at the junction to form an interface with a smaller pore size, thereby simulating the function of the calcified layer, which can not only ensure that the bone marrow blood carries bioactive substances such as bone marrow mesenchymal stem cells and growth factors to penetrate into the cartilage defect site, but also hinder the blood vessel invasion of the subchondral bone repair layer to prevent the calcification of the cartilage layer; and during the repair process, the subchondral bone repair layer provides sufficient support for the repair of the cartilage layer.

[0043] The present invention further improves the performance of the osteochondral scaffold of the present invention having a staggered structure by regulating the printing slurry that forms the cartilage repair layer and the subchondral bone repair layer, thereby avoiding cracking of the scaffold at the junction and improving the mechanical properties, dimensional accuracy and yield rate of the scaffold.

[0044] The present invention further designs the entire stent into a truncated cone-shaped structure, which is easier to implant than a traditional cylindrical stent, and the stent can be stably embedded in the injured area without the need for other fixing methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a stereoscopic diagram of a three-dimensional model of the osteochondral scaffold according to Example 1 of the present invention.

[0046] Figure 2 yes Figure 1 A top view showing the interface structure formed by the interlaced cartilage repair layer and the underlying bone repair layer.

[0047] Figure 3 It is a stereoscopic image of the three-dimensional model of the osteochondral scaffold of Comparative Example 3.

[0048] Figure 4 yes Figure 3 Top view of the .

[0049] Figure 5 1 is a scanning electron microscope image of the interface between the upper layer and the lower layer of the osteochondral scaffold of Example 6 of the present invention.

[0050] Figure 6 The figure is a repair effect diagram of the double-layered osteochondral scaffold of Example 6 of the present invention and the single-layered scaffold of Comparative Example 3 for articular cartilage defects in New Zealand rabbits, in contrast to the blank group.

[0051] Figure 7a This is a staining diagram of a tissue section of the osteochondral scaffold of Example 6 of the present invention used to repair articular cartilage defects in New Zealand rabbits.

[0052] Figure 7b This is a staining diagram of tissue sections of the osteochondral scaffold of Comparative Example 3 used to repair articular cartilage defects in New Zealand rabbits. DETAILED DESCRIPTION

[0053] Various aspects of the present invention will be described in detail below in conjunction with specific embodiments. These specific embodiments are only used to illustrate the present invention and do not constitute any limitation on the protection scope of the present invention.

[0054] In a specific embodiment of the present invention, the cartilage repair layer and the lower bone repair layer in the osteochondral repair scaffold are in an upper and lower two-layer structure, the upper layer repairs the cartilage, and the lower layer repairs the subchondral bone. Among them, the pores of the cartilage repair layer located in the upper layer are mainly vertical pore structures, which are consistent with the arrangement of chondrocytes. In addition, the cartilage repair layer can also increase side holes to facilitate the migration of surrounding cartilage tissue cells to the defect. The pore size of the porous structure of the cartilage repair layer is about 100-1000μm, preferably 600-800μm; the pore wall thickness of the cartilage repair layer is 100-300μm, and the porosity is 50%-80%. In this way, the mechanical strength of the scaffold is guaranteed, while providing more space for cartilage regeneration, and the degradation rate is faster than that of the lower bone repair layer.

[0055] In a specific embodiment of the present invention, the pore size of the porous structure of the lower bone repair layer located in the lower layer is about 300-1000 μm, preferably 400-600 μm. This pore size range is more suitable for bone repair, is conducive to the osteogenic differentiation of stem cells, and promotes the vascularization of bone tissue. The pore wall thickness of the lower bone repair layer is 200-400 μm, and the porosity is 40-60%. The mechanical properties of the lower bone repair layer are better than those of the cartilage repair layer, and the degradation rate is slower than that of the cartilage repair layer, thereby providing sufficient support for the repair of the cartilage layer.

[0056] In a specific embodiment of the present invention, the shapes of the holes in the porous structures of the cartilage repair layer and the underlying bone repair layer can be designed into various shapes, for example, honeycomb, cross, round, square, etc. The junction of the cartilage repair layer and the underlying bone repair layer is formed by interlacing lines (hole walls) to form small holes with a pore size of 50-300 μm, which can simulate the cartilage calcification layer, thereby ensuring that bone marrow blood carrying bioactive substances such as bone marrow mesenchymal stem cells and growth factors penetrate into the cartilage defect site, while also hindering the invasion of underlying blood vessels and preventing calcification of the cartilage layer.

[0057] In a specific embodiment of the present invention, the stent of the present invention is designed as a truncated cone as a whole, with a large diameter at the upper end where the cartilage repair layer is located, and a small diameter at the lower end where the lower bone repair area is located, and the taper is 1:100~1:20. During the surgical operation, it is difficult to keep the drilling hole absolutely perpendicular to the cartilage surface. Even with a very small taper, it will still make it difficult for the cylindrical stent to fit the wound, and additional stress will be generated to cause the stent to break. Compared with traditional cylindrical stents, truncated cone stents are easier to implant and are not easy to break during the repair process, which can improve the repair effect.

[0058] In a specific embodiment of the present invention, the hole walls of the cartilage repair layer and the lower bone repair layer may be chamfered or rounded to reduce the stress between the layers and further improve the mechanical properties of the scaffold.

[0059] In a specific embodiment of the present invention, the bioceramic osteochondrocyte repair scaffold of the present invention is prepared by digital light processing (DLP) 3D printing technology, and the preparation method of the bioceramic osteochondrocyte scaffold based on photocuring 3D printing includes the following steps:

[0060] 1. Design the bracket model:

[0061] Digital 3D model design of osteochondral scaffold: Use 3D design software such as Solidworks, 3Ds Max, Cinema 4D, Maya, Rhinoceros or ZW3D to design a digital 3D model of osteochondral scaffold, convert the model into STL format, and import it into slicing software such as Cura, Simplify3D, PrusaSlicer, 10dim or Magics. The slice thickness is 25-100μm, preferably 30-50μm.

[0062] 2. Prepare printing paste:

[0063] The bioceramic powder, photosensitive resin, photoinitiator, light absorber and dispersant are mixed evenly, and ball-milled in a planetary ball mill for 2-8 hours to obtain a ceramic slurry. The bioceramic powder can be a bioceramic material commonly used in the art, including but not limited to a mixture of one or more of hydroxyapatite, β-tricalcium phosphate, and bioactive glass. Among them, the photosensitive resin, photoinitiator, light absorber and dispersant can be selected from photosensitive resins, photoinitiators, light absorbers and dispersants commonly used in the art.

[0064] Due to the structural differences between the cartilage repair layer and the lower bone repair layer, the osteochondrium scaffold of the present invention is prone to cracking or pore blockage between the upper and lower layers after calcination. In order to further improve the mechanical properties of the scaffold and avoid cracking or pore blockage after calcination, the present invention increases the solid content of the ceramic slurry, and the solid phase volume fraction of the slurry is controlled at 40%~58% (or the weight percentage of the solid phase in the slurry is controlled at 65%~80%). In addition, the present invention further regulates the viscosity of the slurry. High solid content usually leads to increased viscosity of the ceramic slurry, and too high viscosity will cause printing failure. The present invention reduces the viscosity of the slurry by adding a dispersant to the slurry. The dispersant includes but is not limited to: BYK110, BYK111, BYK-180, PX4310, KOS110, RD-9784, S18, oleic acid, KH560, sodium polyacrylate, etc. The mass ratio of the dispersant to the ceramic powder is 1% to 5%, so that the viscosity of the slurry meets the printing requirements. In a specific embodiment of the present invention, the viscosity of the slurry is controlled at 400 to 8580 mP·s.

[0065] In addition, ceramic powders can cause ultraviolet light to scatter during the curing process. The light scattering phenomenon of high solid content slurry is more serious, which can easily lead to over-curing of printing. The present invention can also effectively reduce light scattering and improve printing accuracy by adding light absorbers. Light absorbers include but are not limited to: UV-327, UV-9, UV-531, graphite, etc. The mass percentage of light absorbers in the photosensitive resin is 0.2% to 2%.

[0066] 3. Printing of bracket blank:

[0067] Pour the ceramic slurry into the material tank of the light-curing 3D printer, import the sliced ​​digital model into the execution software to start printing, adjust and optimize the process parameters, and print and prepare the ceramic bracket blank.

[0068] 4. Post-processing of the bracket blank:

[0069] Use ethanol ultrasonic cleaning combined with a spin-drying process to remove the uncured slurry adhering to the surface of the stent and the internal pores, and perform UV curing on the cleaned stent for 2-10 minutes to improve the strength of the green blank.

[0070] 5. Sintering of the stent:

[0071] The solidified bracket was placed in a ceramic crucible, transferred to a muffle furnace, and sintered by gradually increasing the temperature in an air atmosphere. The sintering procedure was 0.5-2 ° The heating rate was increased from room temperature to 200 C / min. ° C, keep warm for 1-2 h to remove the moisture in the scaffold blank; then ° The heating rate was increased from 200 C / min ° C increased to 400 ° C, keep warm for 1-3 h to remove hydrogen and oxygen components in the resin; then ° The heating rate was increased from 400 C / min ° C increased to 600 ° C, keep warm for 1-3 h to remove the carbon in the resin; finally, ° The heating rate was from 600 C / min ° C increased to 1000-1200 ° C, keep warm for 2-4 h to make the bioceramic sintered and dense. The heating rate at each stage should be strictly controlled to prevent the scaffold from cracking due to the rapid discharge of gas.

[0072] 6. Sterilization:

[0073] The stent prepared in step 5 is sterilized by γ-ray irradiation after packaging.

[0074] The present invention is further described below in conjunction with specific embodiments.

[0075] Example 1

[0076] Solidworks software was used to design a truncated cone-shaped double-layer bracket. The three-dimensional model of the bracket is shown in the figure. Figure 1 As shown. The diameter of the upper end of the scaffold where the cartilage repair layer is located is 8mm, the diameter of the lower end where the subchondral bone repair layer is located is 7.7mm, the scaffold height is 10mm, and the corresponding taper is 3:100. The cartilage repair layer has honeycomb vertical holes with a pore size of 600 to 800μm, and the subchondral bone repair layer has cross-shaped holes with a pore size of 400 to 600μm. The pores of the upper and lower layers are staggered at the junction to form small holes of 100 to 300μm, as shown. Figure 2 As shown. The hole wall thickness of the upper scaffold (i.e., cartilage repair layer) is 0.15 mm, and the hole wall thickness of the lower scaffold (i.e., subchondral bone repair layer) is 0.3 mm. The exported STL format file is imported into Magics slicing software, and the TDP slicing file is generated and imported into the 3D printer for printing.

[0077] Preparation of printing slurry: weigh photosensitive resin (60g) (its ingredients are: 1,6-hexanediol diacrylate (50g), trimethylolpropane triacrylate (50g) and trimethylbenzoyl-diphenylphosphine oxide (1g) blended), β-tricalcium phosphate powder (120g), polymer polyurethane dispersant (4g) and graphite light absorber (0.6g) in a ball mill. After ball milling for 4 hours, pour into a brown reagent bottle and store in the dark to form a ceramic slurry. The viscosity of the ceramic slurry was tested using a rotational viscometer. In this slurry, the solid volume percentage is 40% and the slurry viscosity is 410 mP·s.

[0078] The prepared slurry was poured into the material tank for 3D printing, and the 3D printer was set to print with a thickness of 50 μm per layer, an exposure time of 3-15 s, and a light source wavelength of 405 nm.

[0079] After printing, the product was washed with anhydrous ethanol and dried for 24 h to obtain the bracket blank.

[0080] The scaffold blank was placed in a box-type resistance furnace and sintered at 1150 °C for 3 h to obtain a porous osteochondral scaffold.

[0081] After packaging, it is sterilized by γ-ray irradiation.

[0082] After cooling, the appearance, dimensional accuracy, shrinkage, porosity and compressive strength of the scaffold were characterized. The results are shown in Table 1.

[0083] Example 2

[0084] The difference between Example 2 and Example 1 lies in the different solid volume percentage of the ceramic slurry and the slurry viscosity.

[0085] Weigh photosensitive resin (55 g), bioceramic powder (135 g), dispersant (4 g) and light absorber (0.6 g) in a ball mill. After ball milling for 4 h, pour into a brown reagent bottle and store in the dark to form a ceramic slurry. In this slurry, the solid volume percentage is 45% and the slurry viscosity is 553 mP·s.

[0086] The remaining preparation steps and parameters are the same as those in Example 1. The appearance, dimensional accuracy, shrinkage, porosity and compressive strength of the scaffold prepared in Example 2 were characterized. See Table 1 for the results.

[0087] Example 3

[0088] The difference between Example 3 and Example 1 lies in the different solid volume percentage of the ceramic slurry and the slurry viscosity.

[0089] Weigh photosensitive resin (50 g), bioceramic powder (150 g), dispersant (4 g) and light absorber (0.6 g) in a ball mill. After ball milling for 4 h, pour into a brown reagent bottle and store in the dark to form a ceramic slurry. In this slurry, the solid volume percentage is 50%, and the slurry viscosity is 887 mP·s.

[0090] The remaining preparation steps and parameters are the same as those in Example 1. The appearance, dimensional accuracy, shrinkage rate, porosity and compressive strength of the scaffold prepared in Example 3 were characterized. Please refer to Table 1 for the results.

[0091] Example 4

[0092] The difference between Example 4 and Example 1 lies in the different solid volume percentage of the ceramic slurry and the slurry viscosity.

[0093] Weigh photosensitive resin (45 g), bioceramic powder (165 g), dispersant (4 g) and light absorber (0.6 g) in a ball mill. After ball milling for 4 h, pour into a brown reagent bottle and store in the dark to form a ceramic slurry. In this slurry, the solid volume percentage is 55% and the slurry viscosity is 2325 mP·s.

[0094] The remaining preparation steps and parameters are the same as those in Example 1. The appearance, dimensional accuracy, shrinkage, porosity and compressive strength of the scaffold prepared in Example 4 were characterized. Please refer to Table 1 for the results.

[0095] Example 5

[0096] The difference between Example 5 and Example 1 lies in the different solid volume percentage of the ceramic slurry and the slurry viscosity.

[0097] Weigh photosensitive resin (40 g), bioceramic powder (174 g), dispersant (4 g) and light absorber (0.6 g) in a ball mill. After ball milling for 4 h, pour into a brown reagent bottle and store in the dark to form a ceramic slurry. In this slurry, the solid volume percentage is 58%, and the slurry viscosity is 8580 mP·s.

[0098] The remaining preparation steps and parameters are the same as those in Example 1. The appearance, dimensional accuracy, shrinkage rate, porosity and compressive strength of the scaffold prepared in Example 5 were characterized. Please refer to Table 1 for the results.

[0099] Comparative Example 1

[0100] The difference between Comparative Example 1 and Example 1 lies in the different solid volume percentage of the ceramic slurry and the slurry viscosity.

[0101] Weigh photosensitive resin (40 g), bioceramic powder (180 g), dispersant (4 g) and light absorber (0.6 g) in a ball mill. After ball milling for 4 h, pour into a brown reagent bottle and store in the dark to form a ceramic slurry. In this slurry, the solid volume percentage is 60% and the slurry viscosity is 15700 mP·s.

[0102] The remaining preparation steps and parameters are the same as those in Example 1. The appearance, dimensional accuracy, shrinkage rate, porosity and compressive strength of the stent prepared in Comparative Example 1 were characterized. Please refer to Table 1 for the results.

[0103] Comparative Example 2

[0104] The difference between Comparative Example 2 and Example 1 lies in the different solid volume percentage of the ceramic slurry and the slurry viscosity.

[0105] Weigh photosensitive resin (65 g), bioceramic powder (105 g), dispersant (4 g) and light absorber (0.6 g) in a ball mill. After ball milling for 4 h, pour into a brown reagent bottle and store in the dark to form a ceramic slurry. In this slurry, the solid volume percentage is 35% and the slurry viscosity is 332 mP·s.

[0106] The remaining preparation steps and parameters are the same as those in Example 1. The appearance, dimensional accuracy, shrinkage rate, porosity and compressive strength of the stent prepared in Comparative Example 2 were characterized. Please refer to Table 1 for the results.

[0107] Table 1 Performance characteristics of osteochondral scaffolds of Examples 1-5 and Comparative Examples 1-2

[0108]

[0109] From the characterization results of Examples 1-5 in Table 1, it can be seen that when the solid phase volume fraction of the printing slurry is 40%~58% and the slurry viscosity is 400~8580mP·s, the appearance of the osteochondral scaffold is complete, without obvious cracks, the pores are not blocked, and the dimensional accuracy and compressive strength can meet the use requirements.

[0110] It can be seen from the characterization results of Comparative Example 2 in Table 1 that when the solid phase volume fraction in the printing slurry is lower than 40% and the slurry viscosity is lower than 400mP·s, obvious cracks appear at the connection between the upper and lower layers of the osteochondral scaffold, and the dimensional accuracy and compressive strength are significantly deteriorated, which cannot meet the use requirements.

[0111] From the characterization results of Comparative Example 1 in Table 1, it can be seen that when the solid phase volume fraction in the printing slurry is higher than 58% and the slurry viscosity is higher than 15700 mP·s, although the dimensional accuracy and compressive strength of the osteochondral scaffold are obviously better, the slurry viscosity is too high, which increases the difficulty of 3D printing and cleaning, and the pores of the scaffold are blocked, so it cannot meet the use requirements.

[0112] Example 6

[0113] The double-layer stent was designed using ZW3D software. The stent of this embodiment is also a truncated cone-shaped double-layer stent, but the size is reduced. The diameter of the upper end of the stent where the cartilage repair layer is located is 5 mm, the diameter of the lower end where the lower bone repair layer is located is 4.8 mm, the stent height is 5 mm, the corresponding taper is 1:25, the hole wall thickness of the upper stent is 0.15 mm, the hole wall thickness of the lower stent is 0.3 mm, and the porosity is 60.2%.

[0114] The upper cartilage repair layer has honeycomb vertical holes with a pore size of 600-800 μm, and the lower subchondral bone repair layer has cross-shaped holes with a pore size of 400-600 μm. The pores of the upper and lower layers are interlaced at the junction, forming small holes with a pore size of 100-300 μm at the junction. The exported STL format file is imported into the 10dim slicing software, and the TDP slicing file is generated and imported into the 3D printer for printing.

[0115] The ceramic slurry of Example 6 is the same as that of Example 2. The ceramic slurry is poured into the material tank of the light-curing 3D printer, and the truncated cone-shaped bracket model is loaded. The 3D printer is set to print with a thickness of 25 μm per layer, an exposure time of 5-20 s, and a light source wavelength of 405 nm.

[0116] After printing, the product was washed with anhydrous ethanol and dried for 24 h to obtain the bracket blank.

[0117] The bracket blank is placed in a box-type resistance furnace at 1100 ° C for 3 h to obtain a ceramic porous scaffold with a truncated cone double-layer structure. The product is sealed and packaged and sterilized by γ-ray irradiation.

[0118] The double-layer scaffold of Example 6 was observed by scanning electron microscopy (SEM), and its image is as follows: Figure 5 As shown in the figure, it can be seen that the upper layer (cartilage repair layer) and the lower layer (lower bone repair layer) are intertwined, and small holes of 100 ~ 300 μm are formed at the interface between the upper and lower layers by the interlacing of the upper and lower layer lines. The aperture of the small hole formed at the interface (i.e., the third aperture) is smaller than the aperture of the upper layer (i.e., the first aperture) and the aperture of the lower layer (i.e., the second aperture).

[0119] Comparative Example 3

[0120] Comparative Example 3 and Example 6 are the same in overall dimensions, printing slurry, blank printing, sintering and sterilization. The only difference between the two is that: Comparative Example 3 is a truncated cone-shaped single-layer bracket, and its three-dimensional model is as follows: Figure 3As shown, it has cross-shaped holes with a hole diameter of 400~600μm and a hole wall thickness of 0.3mm. The top view of the three-dimensional model of the bracket is shown in Figure 4 As shown in the figure, since the comparative example is a single-layer stent, it does not have the double-layer design of Example 6, and cannot form a small hole structure at the junction of the two layers.

[0121] The sterilized double-layer scaffold of Example 6 and the single-layer scaffold of Comparative Example 3 were used in animal cartilage damage repair experiments to evaluate the effect of the scaffold structure on the cartilage damage repair effect.

[0122] Thirty-six New Zealand rabbits were divided into a blank group, a single-layer scaffold group, and a double-layer scaffold group, with 12 rabbits in each group, for sampling at 6 weeks and 12 weeks, with 6 rabbits at each time point. A 5 mm diameter drill was used to drill holes in the femoral trochlea of ​​the New Zealand rabbits to create a full-thickness cartilage injury model, with a wound diameter of 5 mm and a depth of 5 mm.

[0123] The double-layer stent of Example 6 and the single-layer stent of Comparative Example 3 were implanted into the above-mentioned drilling sites, respectively. The blank group was not implanted with a stent as a control. The rabbits in each group were sampled 6 and 12 weeks after surgery and their morphology was observed. The repair results of the injured site are shown in Figure 2. Figure 6 As shown. Figure 6 It can be seen that after 6 and 12 weeks, the cartilage injury site in the blank group was not repaired, and only some fibrous tissue grew, indicating that the 5 mm diameter cartilage injury in the New Zealand rabbit cannot heal itself. The single-layer scaffold group was not repaired at 6 weeks, and the injury site was filled at 12 weeks, but the surface was not flat and there was a significant difference from the surrounding cartilage tissue, indicating that although the single-layer scaffold had a certain repair effect, it was not ideal. The double-layer scaffold group had achieved filling of the injury site at 6 weeks and complete repair at 12 weeks, and the repaired tissue was well integrated with the normal cartilage.

[0124] The mucosa part in contact with the stent was removed and stained with HE. The results were as follows Figure 7a and Figure 7b As shown. Figure 7a and Figure 7b It can be seen that the staining results of the joint sections of the double-layer scaffold and single-layer scaffold groups showed that the cartilage repair surface in the double-layer scaffold group was smooth and the new cartilage was hyaline cartilage; while the cartilage layer in the single-layer scaffold group showed significant calcification.

[0125] The results of animal experiments show that the double-layer scaffold of the present invention has a significant effect on promoting the repair of cartilage damage and preventing the calcification of the cartilage layer.

[0126] The present invention has been specifically described above in conjunction with specific embodiments. These specific embodiments are only used for illustration and cannot be used to limit the scope of protection of the present invention. Those skilled in the art may make various modifications, changes or substitutions to the present invention without departing from the essence and scope of the present invention. Therefore, various equivalent changes made according to the present invention still belong to the scope covered by the present invention.

Claims

1. Light-curing 3D printed bioceramic bone cartilage scaffold, characterized by: The osteochondral scaffold comprises a cartilage repair layer and a subchondral bone repair layer formed of the same material, wherein: The cartilage repair layer comprises a porous structure with a first pore size, the first pore size is 100-1000 μm, The subchondral bone repair layer comprises a porous structure having a second pore size, wherein the second pore size is 300-1000 μm. The cartilage repair layer and the subchondral bone repair layer are adjacent to each other and are constructed such that: at the junction of the two layers, they are interlaced to form a pore structure with a third pore size, and the third pore size is 50-300 μm; The first aperture, the second aperture and the third aperture satisfy the following conditions: the third aperture is smaller than the first aperture, the third aperture is smaller than the second aperture, and the third aperture size is sufficient to prevent blood vessels from invading the cartilage repair layer; The light-cured 3D printing slurry for forming the cartilage repair layer and the subchondral bone repair layer includes one or more of the following substances: hydroxyapatite, β-tricalcium phosphate, and bioactive glass.

2. The osteochondral scaffold according to claim 1, characterized in that: The first pore size is 600-800 μm.

3. The osteochondral scaffold according to claim 1, characterized in that: The second pore size is 400-600 μm.

4. The osteochondral scaffold according to claim 1, characterized in that: The third pore size is 100-300 μm.

5. The osteochondral scaffold according to claim 1, characterized in that: The porous structure of the cartilage repair layer has a pore wall thickness of 100-300 μm.

6. The osteochondral scaffold according to claim 5, characterized in that: The pore wall thickness of the porous structure of the subchondral bone repair layer is 200-400 μm.

7. The osteochondral scaffold according to claim 1, characterized in that: The osteochondral scaffold is in the shape of a truncated cone as a whole, wherein the cartilage repair layer forms the upper part of the truncated cone, and the subchondral bone repair layer forms the lower part of the truncated cone.

8. The osteochondral scaffold according to claim 7, characterized in that: The taper of the frustum is 1:100-1:

20.

9. The osteochondral scaffold according to claim 1, characterized in that: The cartilage repair layer is mainly composed of a vertical pore structure, which is consistent with the arrangement of chondrocytes.

10. The osteochondral scaffold according to claim 9, characterized in that: The cartilage repair layer is also provided with side holes.

11. The osteochondral scaffold according to claim 1, characterized in that: The porosity of the cartilage repair layer is 50%-80%.

12. The osteochondral scaffold according to claim 1, characterized in that: The porosity of the subchondral bone repair layer is 40%-60%.

13. The osteochondral scaffold according to claim 1, characterized in that: The hole walls of the cartilage repair layer and the subchondral bone repair layer are processed with rounded corners or chamfered corners.

14. The osteochondral scaffold according to claim 1, characterized in that: The solid volume fraction of the photocurable 3D printing slurry that forms the cartilage repair layer and the subchondral bone repair layer is 40% to 58%.

15. The osteochondral scaffold according to claim 14, characterized in that: The viscosity of the light-cured 3D printing slurry that forms the cartilage repair layer and the subchondral bone repair layer is 400~8580mP·s.

16. A method for preparing a light-cured 3D printed bioceramic bone cartilage scaffold, characterized in that: The preparation method comprises the following steps: A scaffold model is established, wherein the scaffold includes a cartilage repair layer and a subchondral bone repair layer, wherein the cartilage repair layer includes a porous structure with a first pore size, and the first pore size is 100-1000 μm; the subchondral bone repair layer includes a porous structure with a second pore size, and the second pore size is 300-1000 μm; the cartilage repair layer and the subchondral bone repair layer are adjacent to each other and are constructed such that: at the junction of the two, they are interlaced to form a pore structure with a third pore size, and the third pore size is 50-300 μm; wherein the first pore size, the second pore size and the third pore size meet the following conditions: the third pore size is smaller than the first pore size, the third pore size is smaller than the second pore size, and the third pore size is sufficient to prevent blood vessels from invading the cartilage repair layer; Preparing a printing slurry for a cartilage repair layer and a subchondral bone repair layer, the slurry comprising ceramic powder, a photosensitive resin, a photoinitiator, a light absorber and a dispersant, wherein the ceramic powder comprises one or more of the following substances: hydroxyapatite, β-tricalcium phosphate, and bioactive glass; Using printing slurry to form a scaffold embryo through 3D printing; The scaffold green body is sintered after post-processing.

17. The preparation method according to claim 16, characterized in that: The solid phase volume fraction in the printing slurry is 40% to 58%.

18. The preparation method according to claim 17, characterized in that: The viscosity of the printing slurry is 400-8580 mP·s.

19. The preparation method according to claim 16, characterized in that: The first pore size is 600-800 μm.

20. The preparation method according to claim 16, characterized in that: The second pore size is 400-600 μm.

21. The preparation method according to claim 16, characterized in that: The third pore size is 100-300 μm.

22. The preparation method according to claim 16, characterized in that: The osteochondral scaffold is in the shape of a truncated cone as a whole, wherein the cartilage repair layer forms the upper part of the truncated cone, and the subchondral bone repair layer forms the lower part of the truncated cone.

23. The preparation method according to claim 22, characterized in that: The taper of the frustum is 1:100-1:20.

Citation Information

Patent Citations

  • Stent for osteochondral defect repair and preparation method thereof

    CN102526809A

  • Ceramic slurry preparation and 3D (three dimensional) printing light curing molding method

    CN106810215A

  • Bone repair material as well as preparation method and application thereof

    CN117679557A